2020
DOI: 10.1111/jace.17048
|View full text |Cite
|
Sign up to set email alerts
|

Toward hard and highly crack resistant magnesium aluminosilicate glasses and transparent glass‐ceramics

Abstract: High hardness and high crack resistance are usually mutually exclusive in glass materials. Through the aerodynamic levitation and laser melting technique, we prepared a series of magnesium aluminosilicate glasses with a constant MgO content, and found a striking enhancement of both hardness and crack resistance with increasing Al2O3. The crack resistance of the magnesium aluminosilicate glass is about five times higher than that of the binary alumina‐silica glass for the similar [Al]/([Al] + [Si]) molar ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Binding energy analysis of Table supports this observation: Mg-OAl 2 has the strongest binding energy among Mg-BO and has the binding energy slightly lower than [3] Mg-NBO and greater than [4] Mg-NBO. Experimental observations also pointed out the higher binding energy of network-modifying cations in aluminosilicate glass to Al-connected oxygen and the binding energy of Mg–O increases especially if the Mg 2+ cations behave as a charge compensator. , …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Binding energy analysis of Table supports this observation: Mg-OAl 2 has the strongest binding energy among Mg-BO and has the binding energy slightly lower than [3] Mg-NBO and greater than [4] Mg-NBO. Experimental observations also pointed out the higher binding energy of network-modifying cations in aluminosilicate glass to Al-connected oxygen and the binding energy of Mg–O increases especially if the Mg 2+ cations behave as a charge compensator. , …”
Section: Resultsmentioning
confidence: 95%
“…Experimental observations also pointed out the higher binding energy of network-modifying cations in aluminosilicate glass to Al-connected oxygen 17 and the binding energy of Mg−O increases especially if the Mg 2+ cations behave as a charge compensator. 16,121 The strength of Mg-OAlSi is weaker than that of Mg-OAl 2 , but the amount of Mg-OAlSi outnumbers that of Mg-OAl 2 , especially at the glass with low MgO and Al 2 O 3 amounts like MAS7612. The dominance of Mg-OAlSi is reasonable as all MAS glass systems in our study contain a significant quantity of Si-O-Al bridges, as shown in Table 8.…”
Section: Coordination Analysis Analysis Of the Reaxff Connection Tabl...mentioning
confidence: 99%
“…Phase diagram of MgO–Al 2 O 3 –SiO 2 ternary system 15 together with the investigated compositions (red balls; (49 − x )MgO• x Al 2 O 3 •51SiO 2 ) in this work and the compositions (blue balls; 11MgO• x Al 2 O 3 •(89 − x )SiO 2 ) in our previous investigation 14 …”
Section: Introductionmentioning
confidence: 68%
“…According to our previous studies, 14 upon the addition of constant 11 molar% MgO into the binary Al 2 O 3 –SiO 2 glassy system shown in Figure 1, 15 the 11MgO•38Al 2 O 3 •51SiO 2 glass exhibits a five times enhancement in crack resistance from 9.69 N for the 45Al 2 O 3 •55SiO 2 glass to 50.22 N for the 11MgO•38Al 2 O 3 •51SiO 2 glass with the similar Al/Si ratio. Herein, on the basis of this composition, by using the aerodynamic levitation and laser heating technique, we extend the glass‐forming region of the magnesium aluminosilicate glasses with the compositions (49 − x )MgO• x Al 2 O 3 •51SiO 2 ( x = 7–49) well from Mg‐rich to peraluminous compositions.…”
Section: Introductionmentioning
confidence: 90%
“…By utilizing the laser-heated aerodynamic levitation setup built in our lab described in detail in our previous reports, [14][15][16] we prepared the sample with the molar composition of 30Al 2 O 3 Á 70SiO 2 having spinodal decomposition peculiarity, whose position in the phase diagram is shown in Fig. 1.…”
Section: Sample Preparationmentioning
confidence: 99%